Creative Dance Improves Physical Fitness and Life Satisfaction in Older Women. (November 2015) - Cruz-Ferreira, Ana; Marmeleira, José; Formigo, Alexandra; Gomes, Dulce; Fernandes, Jorge
Objectives: The purpose of this study was to evaluate the effects of creative dance on physical fitness and life satisfaction in older women. Methods: A total of 57 women (65–80 years old) were randomized to either an experimental group or a control group. The experimental group participated in a supervised creative dance program for 24 weeks. Physical fitness (strength, aerobic endurance, flexibility, motor ability/dynamic balance, and body composition) and life satisfaction were assessed pre- and posttreatment (at 12 and 24 weeks) by the Senior Fitness Test and the Life Satisfaction scale, respectively. Results: After the intervention, the experimental group had better physical fitness and life satisfaction when compared with the control group. Conclusion: Creative dance has a positive effect in different dimensions of functioning and has the potential to contribute to healthy aging. This could be related to the integrated mobilization of physical, cognitive, and social skills promoted by creative dance.